Exchange Rate Pass-Through in the Deflationary Japan: How Effective is the Yen's Depreciation for Fighting Deflation? - Eiji Fujii (Center for Economic Studies and ifo Institute (CESifo), 2004)
There is an increasing endorsement for the yen's depreciation as a means to fight the ongoing deflation in Japan. The idea of generating inflation via depreciation relies on the assumption that exporters pass-through most of the effect of the exchange rate changes to the Japanese importers and consumers. A recent study by Taylor (2000), however, suggests that the rate of the pass-through may have declined in many countries making depreciation of domestic currencies less inflationary. In this study, we estimate the degree of exchange rate pass-through to the Japanese imports, focusing on the recent deflationary period. We then assess quantitatively the expected effectiveness of depreciation in taming the deflation. Our empirical results indicate that the long-run import pass-through has indeed declined significantly. As a result, the inflationary effect of depreciation has been reduced substantially over the past two decades.
Keywords: 330; pass-through; exchange rate; deflation; Japan